2018
DOI: 10.1007/s11920-018-0970-3
|View full text |Cite
|
Sign up to set email alerts
|

Children of Parents with Eating Disorders

Abstract: Despite substantial diversity in study design, sample size, and parental eating disorder definition, overall, existing research suggests that the children of parents with eating disorders exhibit compromised development: a greater risk of perinatal complications; a tendency toward extremes of growth at birth; greater problems in feeding and eating behaviors and greater incidence of eating disorder symptoms; more psychological and socioemotional difficulties; and more negative qualities to parent-child interact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 67 publications
1
31
0
1
Order By: Relevance
“…These are associating episodes of binge eating and compensatory activities (sustained physical exercise) for weight-control purposes. This data agrees with studies of EDs in pregnant women [ 34 36 ]. Several studies in our review found subthreshold types of EDs [ 19 , 21 , 23 , 30 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…These are associating episodes of binge eating and compensatory activities (sustained physical exercise) for weight-control purposes. This data agrees with studies of EDs in pregnant women [ 34 36 ]. Several studies in our review found subthreshold types of EDs [ 19 , 21 , 23 , 30 ].…”
Section: Discussionsupporting
confidence: 93%
“…Mothers with an ED report greater difficulties in determining their child's needs. There is a risk that women with restrictive anorexia nervosa will project their eating and body concerns into their child [ 36 ]. Newborns of mothers with an active ED during pregnancy show difficulties in maintaining their homeostasis when faced with stress factors.…”
Section: Discussionmentioning
confidence: 99%
“…Maternal concern regarding weight and shape does seem, in some, to play a role in the development of disordered eating [ 62 , 88 , 89 ]. A mother with an eating disorder increases the risk of having frank eating disorder psychopathology in a female child, when compared with controls: by age ten, the young person is more likely to diet and hold overvalued ideas about body shape and weight [ 90 ].…”
Section: Families Disturbedmentioning
confidence: 99%
“…Maternal concern regarding weight and shape impacts the family environment [ 88 ], which may be causative in the development of AN. The frequency of negative maternal messages has been associated with the young person experiencing weight and shape concerns, exercise fixation, and eating disorder symptoms [ 89 ].…”
Section: Families Disturbedmentioning
confidence: 99%
“…To date, only one recent systematic review has been published on this topic in the last several years and the authors did focus only on the most recent findings (2015 onwards) (Watson et al 2018 ). Previous reviews focusing on children of mothers with ED include (Patel et al 2002 ) and (Park et al 2003 ).…”
Section: Introductionmentioning
confidence: 99%